2016
DOI: 10.18632/oncotarget.7377
|View full text |Cite
|
Sign up to set email alerts
|

The RNA helicase A in malignant transformation

Abstract: The RNA helicase A (RHA) is involved in several steps of RNA metabolism, such as RNA processing, cellular transit of viral molecules, ribosome assembly, regulation of transcription and translation of specific mRNAs. RHA is a multifunctional protein whose roles depend on the specific interaction with different molecular partners, which have been extensively characterized in physiological situations. More recently, the functional implication of RHA in human cancer has emerged. Interestingly, RHA was shown to coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 101 publications
0
28
0
1
Order By: Relevance
“…A comparison of these data sets shows significant overlap in the identity of gene products affected by the depletion of either protein (287 genes with altered expression upon DHX9 or Nup98 depletion, p=3.24×10 −36 ; see Material and methods), consistent with the idea that these proteins form a functional complex. Interestingly, a significant number (p-value 2.38 × 10 −4 ) of those genes exhibiting altered expression upon Nup98 depletion contain a putative cAMP-response element (CRE) (Zhang et al, 2005), a regulatory element whose transcriptional activity can be regulated by DHX9 (Aratani et al, 2001; Fidaleo et al, 2016; Lee and Pelletier, 2016).
10.7554/eLife.18825.024Figure 11.Nup98 or DHX9 depletion alters the abundance of target mRNAs.HEK293T cells were transduced with a control shRNA or an shRNA targeting Nup98 or DHX9.
…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of these data sets shows significant overlap in the identity of gene products affected by the depletion of either protein (287 genes with altered expression upon DHX9 or Nup98 depletion, p=3.24×10 −36 ; see Material and methods), consistent with the idea that these proteins form a functional complex. Interestingly, a significant number (p-value 2.38 × 10 −4 ) of those genes exhibiting altered expression upon Nup98 depletion contain a putative cAMP-response element (CRE) (Zhang et al, 2005), a regulatory element whose transcriptional activity can be regulated by DHX9 (Aratani et al, 2001; Fidaleo et al, 2016; Lee and Pelletier, 2016).
10.7554/eLife.18825.024Figure 11.Nup98 or DHX9 depletion alters the abundance of target mRNAs.HEK293T cells were transduced with a control shRNA or an shRNA targeting Nup98 or DHX9.
…”
Section: Resultsmentioning
confidence: 99%
“…Given the functional relevance of DHX9 in genomic instability and in cancer [12], we asked whether its expression represents a prognostic factor in Ewing sarcoma. Analysis of event-free survival and overall survival in a dataset comprising 64 Ewing sarcoma, 4 Askin, and 20 perypheral primitive neuroectodermal tumors [25], which all belong to the family of Ewing tumors, showed that high DHX9 expression correlates with worse prognosis of the patients ( Figure 1A,B).…”
Section: Dhx9 Expression Correlates With Worse Prognosis In Ewing Sarmentioning
confidence: 99%
“…However, reduction in the RNAPII elongation rate within the DHX9 transcription unit favors exon 6A inclusion and targets the transcript to NMD [11]. Both UV light irradiation and etoposide treatment induced this event by slowing down the RNAPII [11], with the consequent decrease in DHX9 expression, thus leading to higher sensitivity of Ewing sarcoma cells to genotoxic stress [11,12]. Nevertheless, the mechanism by which exon 6A inclusion is normally repressed in Ewing sarcoma cells is currently unknown.DHX9 is a member of the DExH subgroup of RNA helicases, which play important roles in several aspects of RNA metabolism [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations